Non-Formal Musical Education in the Context of Children’s Experiences: Involving or Limiting? - Kriščiūnaitė, Asta; Strakšienė, Diana; Bubnys, Remigijus (Pedagogika, 2018)
The article deals with analysis of experiences of music school students through focusing on the threat of involvement and discrimination (in the context of the problem of political and practical dualism) by employing the conception of universal education design. Analysis of the research data revealed students’ primary experiences in music school, identification of teacher’s behavior in the process of teaching and learning which significantly contributed to (non-)involvement and (non-)limitation of students as well as manifestation of formal assessment in the education process. Summing up, an assumption is drawn that non-formal music education of children is still incapable of full-fledged involvement of children and prevention from discrimination while meeting their individual needs; however, it aims at higher integration of children into the system, i.e. not to adjust the system to the learners but rather to adapt the learners to the system.